Peran pendidikan dalam pembentukan identitas masyarakat modern - Al Maulani, Siti anisa; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
The development of globalization and advances in digital technology have had a major influence on the way society builds its identity and culture. In this context, education plays an important role as the main forum for the formation of moral values, character and national spirit in the midst of continuously developing global cultural flows. This research uses a qualitative method with a library research approach through the study of various scientific sources that discuss the themes of education, socio-cultural identity and the impact of globalization. The results of the study show that the application of multicultural education and citizenship education can foster attitudes of tolerance, empathy and a strong sense of nationalism. Apart from that, the use of information technology in the teaching and learning process opens up opportunities for educational innovation, but requires increased digital literacy so that students are able to think critically and wisely in filtering foreign cultural influences. Based on these findings, it can be concluded that education does not only function to transfer knowledge, but is also the main foundation in forming a strong and responsive national character and identity to global dynamics.